Multiple sclerosis and herpesvirus interaction - Guilherme Sciascia do Olival; Bruna Mendonca Lima; Laura M. Sumita; Vitor Serafim; Maria Cristina Fink; Luis Henrique Nali; Camila Malta Romano; Rodrigo Barbosa Thomaz; Vitor Breseghello Cavenaghi; Charles Peter Tilbery; Augusto Cesar Penalva-de-Oliveira (Arquivos de Neuro-Psiquiatria, 2013)
Multiple sclerosis is the most common autoimmune inflammatory demyelinating disease of the central nervous system, and its etiology is believed to have both genetic and environmental components. Several viruses have already been implicated as triggers and there are several studies that implicate members of the Herpesviridae family in the pathogenesis of MS. The most important characteristic of these viruses is that they have periods of latency and exacerbations within their biological sanctuary, the central nervous system. The Epstein-Barr, cytomegalovirus, human herpesvirus 6 and human herpesvirus 7 viruses are the members that are most studied as being possible triggers of multiple sclerosis. According to evidence in the literature, the herpesvirus family is strongly involved in the pathogenesis of this disease, but it is unlikely that they are the only component responsible for its development. There are probably multiple triggers and more studies are necessary to investigate and define these interactions.